2009
DOI: 10.1086/644613
|View full text |Cite
|
Sign up to set email alerts
|

The Polonium Brief: A Hidden History of Cancer, Radiation, and the Tobacco Industry

Abstract: The first scientific paper on polonium-210 in tobacco was published in 1964, and in the following decades there would be more research linking radioisotopes in cigarettes with lung cancer in smokers. While external scientists worked to determine whether polonium could be a cause of lung cancer, industry scientists silently pursued similar work with the goal of protecting business interests should the polonium problem ever become public. Despite forty years of research suggesting that polonium is a leading carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…De maneira geral, a relação entre o 210 Po e o tabaco diverge em datas de publicação do primeiro estudo. Rego (2009) descreve como sendo a primeira publicação sobre o assunto datada de 1964, havendo nas décadas seguintes outros trabalhos ligando radioisótopos e tabagismo.…”
Section: Métodos De Detecção Desenvolvidosunclassified
“…De maneira geral, a relação entre o 210 Po e o tabaco diverge em datas de publicação do primeiro estudo. Rego (2009) descreve como sendo a primeira publicação sobre o assunto datada de 1964, havendo nas décadas seguintes outros trabalhos ligando radioisótopos e tabagismo.…”
Section: Métodos De Detecção Desenvolvidosunclassified
“…5,13 Despite studies documenting the appearance of lung cancer in animals exposed to low dose of 210 Po, 12 the tobacco industry made no successful effort to remove 210 Po and 210 Pb from tobacco. 7,14,15 Studies on the role of 222 Rn and its progeny as a cause of lung cancer have demonstrated a synergetic effect with tobacco smoke, with efforts to reduce in-house 222 Rn bene ciating more to smokers. [16][17][18] In this respect, it appears that 210 Po present in tobacco smoke could be responsible of some lung cancers otherwise attributed to radon.…”
Section: Introductionmentioning
confidence: 99%
“…8,19 As a matter of fact, Winters and Difranza reported "having received hundreds of phone calls from smokers who quit on learning about alpha radiation in cigarette smoke", after the publication of a letter denouncing the lack of research on 210 Po in tobacco in The New England Journal of Medicine. 2,7,20 Thus, the presence of radioactivity in tobacco products and tobacco smoke could be a valuable argument for smoking cessation and could be used as an additional public heath intervention to reduce smoking prevalence tobacco-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Although research indicating polonium as one of the major tobacco carcinogens is encouraging, a recent systematic review of this issue has shown that the study of radioactivity of tobacco smoke has been scientifically stagnant for 40 years. On the other hand, the extent to which the tobacco industry has understood the risks of polonium and has discussed its implications is impressive [11,12].…”
Section: Introductionmentioning
confidence: 99%